Fibrewise I-proximity Space. Issue 5 (4th July 2021) - Abdulsada, Dheargham Ali; Zghair, Hayder Kadhim
Abstract: The main idea of this research is to consider Fibrewise I-proximity Space as well as, introduce fibrewise ρ -map and a I -proximal neighbourhood, Likewise those p-continuous maps continuous with respect to the induced topologies, Accordingly each Fibrewise I-proximity Space is a fibrewise topological space, Additionally more important separation axioms in there spaces, are characterized and a few outcomes are demonstrated.